User satisfaction associated with speech therapy in Family and Community Health organizations - del Campo Rivas, Manuel; Silva-Ríos, Angélica Pilar (Revista de Investigación en Logopedia, 2022)
User satisfaction represents a relevant dimension of quality in health and is an indispensable area for the provision of effective health services. The objective of this study is to characterize the satisfaction of people who receive speech therapy in family and community health organizations. A mixed sequential explanatory study was carried out with a descriptive cross-sectional phase that included the calculation of frequencies complemented with the application of semi-structured interviews for the identification of categories of meaning from content analysis. The results regarding the perceived quality of care, 85% reported having been treated within adequate times, 98.3% reported being treated with dignity and 85% perceived an increase in their quality of life. As for health organizations, 28.3% reported having waited more than 5 minutes for care and 73.3% that their sessions were carried out in 30-minute sessions. From the technical quality and safety of the user, 88.3% reported that the care was of quality and the same percentage reported that the work in the health team was coordinated. Three categories of meaning related to active listening, social participation and implemented socio-cultural adjustments were identified. As a conclusion it ca be said that there is high satisfaction on the part of people attended by speech therapists in family and community health centers. The description of satisfaction provides feedback on speech therapy and invites the consolidation of actions aligned with family and community health strategies in the territory.
Keywords: Patient Satisfaction; Speech and Language Pathology; Primary Health Care; Community Health Services